Implikasi Penerbitan Omnibus Law Undang-Undang Nomor 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan (UU P2SK) Terhadap Peran Otoritas Jasa Keuangan (OJK) dalam Sektor Keuangan - Yuliana Syafitri (LPPM Universitas Ekasakti Padang, 2023)
The issuance of the omnibus law in overcoming hyperregulation conditions has led to a long discussion in Indonesia. This is because the omnibus method is commonly used in countries that use the common law legal system. Meanwhile, Indonesia uses a civil law legal system that prioritizes codification as a solution to the hyper-regulation problem. However, Indonesia continues to adopt the omnibus method through one of which is the issuance of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UUP2SK). This has an impact on the role of OJK in supervising the financial sector in Indonesia. The results of the research show that there is additional authority possessed by the OJK. In addition, its independence is also enhanced to realize financial climate stability.